A kind of iron phosphate precursor and preparation method thereof, lithium iron phosphate positive electrode material and lithium ion battery
By simplifying the process, iron ore, phosphorus source and acid are mixed for a hydrothermal reaction to prepare a hexagonal layered iron phosphate precursor, which solves the problems of complex processes and high raw material requirements in the existing technology, and achieves Preparation of low-cost iron phosphate precursor suitable for large-scale production and improved electrochemical performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202310188134.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-01
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-03-01
AI Technical Summary
The existing preparation method of lithium iron phosphate positive electrode material has a complex process route and high requirements for raw materials, making it difficult to meet the needs of large-scale industrial production.
By mixing iron ore, phosphorus source and acid, hydrothermal reaction and solid-liquid separation are performed to prepare a hexagonal lamellar iron phosphate precursor, which reduces raw material costs and process complexity.
The preparation of iron phosphate precursor with lower cost and higher raw material adaptability is achieved, which is suitable for large-scale industrial production and improves the electrochemical performance of lithium-ion batteries.
Smart Images

Figure CN116332142B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to an iron phosphate precursor and a preparation method thereof, a lithium iron phosphate positive electrode material and a lithium-ion battery. Background Art
[0002] Lithium iron phosphate has become the most promising cathode material at present due to its advantages such as low synthesis cost, non-toxicity and good stability, and has received extensive attention from commercial organizations and scientific and technological workers. With the widespread application of lithium-ion batteries in high-power hybrid vehicles and energy storage power stations, higher and higher requirements have been placed on the performance of cathode materials. Compared with traditional lithium-ion cathode materials such as lithium cobalt oxide, lithium manganese oxide, and lithium nickel oxide, lithium iron phosphate is undoubtedly the first choice for large-capacity, high-power, long-life, economical and environmentally friendly power battery cathode materials among the cathode materials currently being studied because of its advantages such as low price, environmental friendliness, good thermal stability, abundant resources, and safe performance.
[0003] At present, in the process of synthesizing lithium iron phosphate cathode materials, iron phosphate is an important precursor. It is a key factor affecting the performance of lithium iron phosphate cathode materials and plays an important role in the process of studying the electrical properties of lithium iron phosphate cathode materials. However, the existing preparation methods have problems such as complex process routes and high requirements for raw materials. Summary of the invention
[0004] The purpose of the present invention is to provide an iron phosphate precursor and a preparation method thereof, a lithium iron phosphate positive electrode material and a lithium ion battery. The iron phosphate precursor is prepared by a simple process using low-priced and widely available iron ore as a raw material, which has lower cost, higher raw material adaptability, and is suitable for large-scale industrial production. The lithium battery prepared using the iron phosphate precursor as a raw material also has good electrochemical performance.
[0005] To achieve the above objectives, the technical solution of this application is as follows:
[0006] In a first aspect, the present application provides an iron phosphate precursor, the iron phosphate precursor comprising hexagonal lamellar primary particles.
[0007] In some preferred embodiments, a plurality of primary particles of hexagonal sheets are stacked to form secondary particles, and the structure of the secondary particles includes hexagonal prisms.
[0008] In some preferred embodiments, at least one of the following conditions is met:
[0009] a. The thickness of the hexagonal prism is 30nm-200nm;
[0010] b. The side length of the hexagonal prism is 0.5μm-4μm;
[0011] c. The maximum internal angle in a hexagonal prism ranges from 120° to 155°.
[0012] In some preferred embodiments, the iron-to-phosphorus ratio of the iron phosphate precursor is 0.94-1.
[0013] In a second aspect, the present application provides a method for preparing an iron phosphate precursor, comprising:
[0014] mixing iron ore, a phosphorus source and an acid to obtain a mixed solution;
[0015] After the mixed solution is subjected to hydrothermal reaction and solid-liquid separation, the solid product is washed and dried to obtain an iron phosphate precursor.
[0016] In combination with the first aspect, as some optional implementations of the present application, the preparation method satisfies at least one of the following conditions:
[0017] d. The mixed solution further comprises a surfactant;
[0018] e. The acid comprises at least one of nitric acid, sulfuric acid and hydrochloric acid;
[0019] f. The iron ore includes at least one of hematite, magnetite, limonite, siderite, phosphite and iron sulfide;
[0020] g. The phosphorus source comprises at least one of phosphoric acid and phosphate;
[0021] h. The solid content concentration of the iron ore in the mixed solution is 25g / L-65g / L;
[0022] i. The concentration of the acid in the mixed solution is 1 mol / L-5 mol / L;
[0023] j. The molar ratio between the iron element in the iron ore and the phosphorus element in the phosphorus source is 1:(1-6).
[0024] In some preferred embodiments, the preparation method satisfies at least one of the following conditions:
[0025] k. The surfactant comprises at least one of hexadecyltrimethylammonium bromide and dodecyltrimethylammonium bromide;
[0026] l. The phosphate includes at least one of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate;
[0027] m. The concentration of the surfactant in the mixed solution is 1g / L-15g / L.
[0028] As some optional embodiments of the present application, the preparation method further satisfies at least one of the following conditions:
[0029] n. The pH value of the solution after the hydrothermal reaction is 0.2-2;
[0030] o. The temperature of the hydrothermal reaction is 110°C-170°C;
[0031] p. The hydrothermal reaction time is 2h-8h.
[0032] In a third aspect, the present application provides a lithium iron phosphate positive electrode material, the raw material of which includes the iron phosphate precursor described in the first aspect or the iron phosphate precursor prepared by the preparation method described in the second aspect.
[0033] In a fourth aspect, the present application also provides a lithium-ion battery, the raw materials of which include the lithium iron phosphate positive electrode material described in the third aspect.
[0034] Beneficial effects of this application:
[0035] The iron phosphate precursor of the present application includes hexagonal lamellar primary particles, which have a higher tap density than the iron phosphate precursor with disordered primary particles, increase the discharge capacity per unit volume, and improve the energy density per unit volume, so that the battery has good electrochemical performance. In addition, the structure of the secondary particles formed by stacking multiple hexagonal lamellar primary particles is a hexagonal prism, the integrity of the primary particles is good, and the stacked hexagonal prism layers are thicker, which further improves the performance of the prepared battery.
[0036] In the preparation method of the iron phosphate precursor of the present application, compared with the method of using high-purity iron salt and phosphorus source to prepare the iron phosphate precursor in the prior art, on the one hand, the raw materials used in the present application are low in price and widely available, which effectively reduces energy consumption and cost, while the high-purity iron source in the prior art is expensive, affecting the market competitiveness of the production of iron phosphate; on the other hand, the present application uses a hydrothermal method to crystallize under the coexistence of gas, liquid and solid three-phase conditions, which improves the purity of iron phosphate crystallization and overcomes the drawbacks caused by impure raw materials, while the crystallization reaction of the prior art under normal pressure will affect the purity of the generated iron phosphate. Therefore, the preparation method of the present application has a simple process, directly uses lower-priced iron ore as raw material, which not only improves the value of the iron ore itself, but also is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope of the present invention.
[0038] Figure 1This is a SEM image of the iron phosphate precursor obtained in Example 4;
[0039] Figure 2 This is a SEM image of the iron phosphate precursor obtained in Example 5;
[0040] Figure 3 This is a SEM image of the iron phosphate precursor obtained in Example 6;
[0041] Figure 4 This is a SEM image of the iron phosphate precursor obtained in Example 7;
[0042] Figure 5 The XRD spectrum of the iron phosphate precursor obtained in Example 6;
[0043] Figure 6 This is the TG-DTG spectrum of the iron phosphate precursor obtained in Example 6. DETAILED DESCRIPTION
[0044] As used herein:
[0045] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0046] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0047] In these examples, parts and percentages are by mass unless otherwise indicated.
[0048] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0049] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0050] In a first aspect, the present application provides an iron phosphate precursor, which includes a plurality of hexagonal lamellar primary particles. The hexagonal lamellar structure makes the material have a higher tap density, increases the discharge capacity per unit volume, and improves the energy density per unit volume, so that the battery has good electrochemical performance.
[0051] In some preferred embodiments, a plurality of primary particles of hexagonal sheets are stacked to form secondary particles, and the structure of the secondary particles includes hexagonal prisms, which further improves the performance of the prepared battery.
[0052] In some preferred embodiments, the thickness of the hexagonal prism is 30 nm-200 nm, for example, 30 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm or any value between 30 nm and 200 nm, more preferably between 100 nm and 200 nm.
[0053] In some preferred embodiments, the side length of the hexagonal prism is 0.9 μm-4 μm, for example, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm or any value between 0.9 μm and 4 μm, more preferably between 0.94 μm and 2.5 μm.
[0054] In some preferred embodiments, the maximum internal angle in the hexagonal prism is in the range of 120°-155°, more preferably in the range of 120°-130°, which mainly indicates that the hexagonal sheet structure is a regular hexagon-like structure.
[0055] In some preferred embodiments, the iron-phosphorus ratio of the iron phosphate precursor is 0.94-1. The iron-phosphorus ratio refers to the molar ratio of the iron element to the phosphorus element.
[0056] In a second aspect, the present application provides a method for preparing an iron phosphate precursor, comprising:
[0057] S1, mixing iron ore, a phosphorus source and an acid to obtain a mixed solution;
[0058] S2. After subjecting the mixed solution to hydrothermal reaction and solid-liquid separation, the solid product is washed and dried to obtain an iron phosphate precursor.
[0059] In combination with the first aspect, in some optional embodiments, the iron ore in S1 includes at least one of hematite, magnetite, limonite, siderite, phosphotyrite, and iron sulfide. It should be noted that in the preparation method of the present application, it is not necessary to remove impurities from the iron ore.
[0060] In some optional embodiments, the phosphorus source in S1 includes at least one of phosphoric acid and phosphate.
[0061] Further preferably, the phosphate includes at least one of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.
[0062] In some optional embodiments, the acid in S1 includes at least one of nitric acid, sulfuric acid, and hydrochloric acid, more preferably nitric acid.
[0063] In some optional embodiments, the solid content concentration of iron ore in S1 in the mixed solution is 25g / L-65g / L, for example, it can be 25g / L, 30g / L, 35g / L, 40g / L, 50g / L, 60g / L, 65g / L or any value between 25g / L and 65g / L.
[0064] In some optional embodiments, the concentration of the acid in S1 in the mixed solution is 1 mol / L-5 mol / L, for example, it can be 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or any value between 1 mol / L and 5 mol / L.
[0065] In some optional embodiments, the molar ratio between the iron element in the iron ore and the phosphorus element in the phosphorus source is 1:(1-6), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6 or any value in between 1:(1-6).
[0066] In some optional embodiments, the mixed solution in S1 further includes a surfactant.
[0067] In some preferred embodiments, the surfactant includes at least one of hexadecyltrimethylammonium bromide and dodecyltrimethylammonium bromide.
[0068] In some preferred embodiments, the concentration of the surfactant in the mixed solution is 1g / L-15g / L, for example, it can be 1g / L, 3g / L, 5g / L, 8g / L, 10g / L, 12g / L, 15g / L or any value between 1g / L and 15g / L.
[0069] In some optional embodiments, the pH value of the solution system after the hydrothermal reaction in S2 is 0.2-2, for example, it can be 0.2, 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2 or any value between 0.2 and 2, more preferably 0.5.
[0070] In some optional embodiments, the temperature for the hydrothermal reaction in S2 is 110°C-170°C, for example, 110°C, 120°C, 130°C, 150°C, 170°C or any value between 110°C and 170°C, more preferably 150°C.
[0071] In some optional embodiments, the time for the hydrothermal reaction in S2 is 2 h-8 h, for example, it can be 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h or any value between 2 h and 8 h, more preferably 4 h.
[0072] It should be noted that when the added P / Fe=1.5 and the reaction temperature is 150°C, products with higher iron conversion rates and phosphoric acid conversion rates can be prepared. At the same time, when the pH value of the solution system after the hydrothermal reaction is 0.5, the crystallization process of iron phosphate is under high acidity, and the solubility product constant of the impurity ions in the mixed solution and the phosphate ions to produce precipitation increases, and it is difficult to generate corresponding impurity precipitates, so the prepared product has high purity; when the pH value is less than 0.5, the impurity content of the product will not increase, but the conversion rate will decrease.
[0073] In some optional embodiments, the washing in S2 includes: repeatedly washing the solid product with water until the pH value of the washing solution is 6.5-7.5; and the temperature during drying is 40°C-105°C, more preferably 60°C.
[0074] Specifically, the product after the hydrothermal reaction is filtered, and after the filtration, the solid product is washed multiple times with deionized water until the pH value of the washing solution is 6.5-7.5, and then dried at 60° C. to obtain an iron phosphate precursor.
[0075] In the third aspect, the present application can prepare a lithium iron phosphate positive electrode material by using the iron phosphate precursor described in the first aspect as a raw material, or using the iron phosphate precursor prepared by the preparation method described in the second aspect as a raw material, and apply the lithium iron phosphate positive electrode material to a lithium-ion battery.
[0076] The embodiments of the present invention will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0077] Example 1
[0078] This embodiment provides an iron phosphate precursor, and the specific preparation method thereof includes:
[0079] (1) Mix magnetite, a phosphorus source, and nitric acid to obtain a mixed solution. The volume of the mixed solution is set to 50 mL. In the mixed solution, the solid content concentration of magnetite is 50 g / L, the concentration of nitric acid is 3 mol / L, and the molar ratio of iron in magnetite to phosphorus in the phosphorus source is 1:2. Phosphoric acid is used as the phosphorus source, and the initial concentration of phosphoric acid is 1.27 mol / L. The required mass of each substance is obtained by calculation, weighed, added with water and stirred evenly, and a mixed solution is prepared. Among them, the mass of magnetite is 2.5 g, and the iron element in the magnetite has been quantitatively detected and analyzed.
[0080] (2) The mixed solution was transferred into a 100 mL polytetrafluoroethylene reactor and placed in a homogeneous reactor for reaction at 110 °C for 4 h.
[0081] (3) After the reaction is completed, the pH value of the solution in the test reactor is about 0.5, and then the obtained product is filtered and the solid product is repeatedly washed with deionized water until the pH value of the washing solution is 6.5-7.5, and then dried at 60° C. to obtain the final iron phosphate precursor.
[0082] Example 2
[0083] This embodiment provides an iron phosphate precursor, and its specific preparation method is the same as that of Example 1, except that: in step (1), magnetite is changed to hematite, the iron element in the hematite has been quantitatively detected and analyzed, the molar ratio of iron element to phosphorus element is 1:1.1, the initial concentration of phosphoric acid is 0.7 mol / L, and the reaction temperature of step (2) is 150°C.
[0084] Example 3
[0085] This embodiment provides an iron phosphate precursor, and its specific preparation method is the same as that of Example 1, except that: 0.1 g of CTAB is added in step (1), and the molar ratio of iron element to phosphorus element is 1:1.3, the initial concentration of phosphoric acid is 0.82 mol / L, and the reaction temperature of step (2) is 150°C.
[0086] Example 4
[0087] This embodiment provides an iron phosphate precursor, and its specific preparation method is the same as that of Embodiment 1, except that: the reaction temperature of step (2) is 130°C.
[0088] Example 5
[0089] The present embodiment provides an iron phosphate precursor, and its specific preparation method is the same as that of Example 1, except that: the concentration of nitric acid in step (1) is 4 mol / L, magnetite is converted into limonite, the iron element in the limonite has been quantitatively detected and analyzed, the molar ratio of iron element to phosphorus element is 1:1.5, the initial concentration of phosphoric acid is 0.75 mol / L, the concentration of diammonium dihydrogen phosphate is 0.2 mol / L, the reaction temperature in step (2) is 150°C, and the pH of the solution after the reaction is completed is about 0.2.
[0090] Example 6
[0091] This embodiment provides an iron phosphate precursor, and its specific preparation method is the same as that of Example 1, except that: the molar ratio of iron element to phosphorus element in step (1) is 1:1.5, the initial concentration of phosphoric acid is 0.95 mol / L, and the reaction temperature in step (2) is 150°C.
[0092] Example 7
[0093] The present embodiment provides an iron phosphate precursor, and its specific preparation method is the same as that of Example 1, except that: the concentration of nitric acid in step (1) is 2 mol / L, the molar ratio of iron element to phosphorus element is 1:1.5, the initial concentration of phosphoric acid is 0.95 mol / L, the reaction temperature in step (2) is 150°C, and the pH of the solution after the reaction is completed is about 0.8.
[0094] Table 1 below shows the relevant test results of the iron phosphate precursors prepared in Examples 1-7, and Table 2 shows the technical requirements for battery-grade iron phosphate specified in the industry standard and the relevant test results of the iron phosphate precursors prepared in Examples 5-7.
[0095] Table 1
[0096] Experimental Results Iron conversion rate Phosphoric acid conversion rate Example 1 61.97% 30.985% Example 2 90.02% 45.01% Example 3 89.17% 44.59% Example 4 83.16% 41.58% Example 5 88.20% 44.1% Example 6 90.02% 60.01% Example 7 81.36% 54.24%
[0097] As can be seen from Table 1, among Examples 1-7, the values of the iron conversion rate and the phosphoric acid conversion rate of Example 6 are the highest, indicating that under the preparation process of Example 6, as much iron as possible in the iron ore and the phosphorus in the phosphorus source can be converted into iron phosphate precursors, which can further save costs; at the same time, hematite and limonite are used in Examples 2 and 5. The test results show that different types of iron ores can be prepared into iron phosphate precursors by the preparation method of the present application.
[0098] Table 2
[0099]
[0100]
[0101] As can be seen from Table 2, in the iron phosphate precursors produced in Examples 5-6, the mass contents of iron and phosphorus are between 28.5% and 30.0%, the iron-phosphorus ratio is between 0.96-1.02, and the water content and tap density are within the industry standard range, meeting the requirements of battery-grade iron phosphate; when the hydrothermal reaction is carried out in Example 7, the concentration of nitric acid in the mixed solution is slightly lower, so that the iron content in the iron phosphate product after the reaction is completed is slightly lower than the requirements of battery-grade iron phosphate. It can be seen that when the molar ratio of iron element to phosphorus element is 1:1.5, the mixed solution is subjected to hydrothermal reaction under appropriate acidity to prepare a battery-grade iron phosphate precursor.
[0102] Figure 1-Figure 4 The SEM images of the iron phosphate prepared in Examples 4-7 are listed respectively, which are images taken at the same magnification. Figure 1 The iron phosphate precursor includes a plurality of hexagonal lamellar primary particles, and the secondary particles formed by stacking the plurality of hexagonal lamellar primary particles present a hexagonal prism structure. In the example shown in the figure, ∠d2c2b2 is 130°, ∠a2b2c2 is 120°, the length of b2c2 is 3.24 μm, the length of a2b2 is 3.2 μm, the length of d2c2 is 3.67 μm, and the thickness of the hexagonal prism is 30-120 nm. Figure 2 The primary particles of the iron phosphate precursor are hexagonal lamellar. In the example in the figure, ∠a3b3c3 is 135°, b3c3 is 1.64 μm long, a3b3 is 2.22 μm long, and the thickness of the stacked hexagonal prisms is relatively thin, at 50-70 nm. Figure 3 The iron phosphate precursor includes a plurality of hexagonal lamellar primary particles, wherein the secondary particles formed by stacking the plurality of hexagonal lamellar primary particles are in the shape of a hexagonal prism. The integrity of the primary particles in this structure is good. In the example shown in the figure, ∠ABC and ∠bcd are approximately 123°, ∠fgh is approximately 130°, the length of bc is 1.16 μm, the length of dc is 2.39 μm, the length of fg is 1.99 μm, the length of gh is 0.94 μm, and the thickness of a single lamellar layer is 100-200 nm. Figure 4 The iron phosphate precursor has an irregular flake structure.
[0103] The iron phosphate precursor prepared in Example 4-7 was ball-milled with lithium carbonate and glucose in the ratio of iron phosphate: lithium carbonate: glucose = 1:0.5:0.505 (molar ratio), and dried. After high-temperature solid-phase reaction sintering under the protection of an inert atmosphere, a carbon-coated lithium iron phosphate positive electrode material was obtained. Then, a positive electrode material was prepared by slurrying according to LiFePO4: PVDF: conductive carbon black = 8:1:1 (mass ratio). Lithium metal was used as the negative electrode. The batteries were assembled into lithium-ion button cells, and the electrochemical properties were tested. The specific test results are shown in Table 3.
[0104] Table 3
[0105]
[0106] As can be seen from Table 3, the iron phosphate precursor prepared in Examples 4-6 is used as a raw material to prepare a lithium iron phosphate positive electrode material, and the electrochemical performance of the positive electrode material assembled into a lithium ion battery is good, among which the electrochemical performance of the lithium ion battery assembled in Example 6 is relatively the best, with a first efficiency of 99.73%, a cycle performance of 97.6%, and an initial discharge capacity of 150.1 mAh / g; the cycle performance and initial discharge capacity of Example 7 are relatively low. It can be seen that since the primary particles of the iron phosphate precursor prepared in Examples 4-6 are relatively regular hexagonal sheets, the material tap density is higher, the discharge capacity per unit volume is increased, and the energy density per unit volume is increased, so that the battery has good electrochemical performance; among the iron phosphate precursor prepared in Example 6, the integrity of the primary particles of multiple hexagonal sheets is better, and the stacked hexagonal prism sheets are thicker, which further improves the performance of the prepared battery.
[0107] Figure 6 In the TG-DTG spectrum of the iron phosphate precursor prepared in Example 6 given in the above, an obvious endothermic peak appears near 200°C, accompanied by a mass loss of 18.98%. This peak indicates the process of the sample losing crystal water, and 1.97 H2O in the sample is calculated from the mass loss; combined with Figure 5 The XRD test spectrum diffraction peak shape is consistent with the FePO4 standard card (PDF 84-0876), indicating that the prepared sample is iron orthophosphate (FePO4·2H2O) containing two crystal waters. Figure 5 The XRD spectrum further demonstrates that the iron phosphate precursor prepared using iron ore as raw material in the present application has high purity and is suitable for further preparing lithium iron phosphate positive electrode materials with excellent electrochemical properties.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
[0109] In addition, those skilled in the art will appreciate that although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present invention and form different embodiments. For example, any of the above-mentioned claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present invention and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. An iron phosphate precursor, characterized in that: The iron phosphate precursor includes hexagonal lamellar primary particles; A plurality of primary particles of the hexagonal sheets are stacked to form secondary particles, wherein the structure of the secondary particles includes hexagonal prisms; The thickness of the hexagonal prism is 30nm-200nm; The method for preparing the iron phosphate precursor comprises: mixing iron ore, a phosphorus source and an acid to obtain a mixed solution; After subjecting the mixed solution to a hydrothermal reaction and solid-liquid separation, the solid product is washed and dried to obtain an iron phosphate precursor; The molar ratio between the iron element in the iron ore and the phosphorus element in the phosphorus source is 1:(1-2); The concentration of the acid in the mixed solution is 3 mol / L-5 mol / L; The temperature of the hydrothermal reaction is 110°C-170°C.
2. The iron phosphate precursor according to claim 1, characterized in that At least one of the following conditions is met: a. The side length of the hexagonal prism is 0.9μm-4μm; b. The maximum internal angle of the hexagonal prism is in the range of 120°-155°.
3. The iron phosphate precursor according to any one of claims 1 to 2, characterized in that The iron-phosphorus ratio of the iron phosphate precursor is 0.94-1.
4. A method for preparing an iron phosphate precursor according to any one of claims 1 to 3, characterized in that: include: mixing iron ore, a phosphorus source and an acid to obtain a mixed solution; After subjecting the mixed solution to a hydrothermal reaction and solid-liquid separation, the solid product is washed and dried to obtain an iron phosphate precursor; The molar ratio between the iron element in the iron ore and the phosphorus element in the phosphorus source is 1:(1-2); The concentration of the acid in the mixed solution is 3 mol / L-5 mol / L; The temperature of the hydrothermal reaction is 110°C-170°C.
5. The preparation method according to claim 4, characterized in that: The preparation method satisfies at least one of the following conditions: c. The mixed solution further comprises a surfactant; d. The acid comprises at least one of nitric acid, sulfuric acid and hydrochloric acid; e. The iron ore includes at least one of hematite, magnetite, limonite, siderite, phosphite and iron sulfide; f. The phosphorus source comprises at least one of phosphoric acid and phosphate; g. The solid content concentration of the iron ore in the mixed solution is 25g / L-65g / L.
6. The preparation method according to claim 5, characterized in that: The preparation method satisfies at least one of the following conditions: h. The surfactant comprises at least one of hexadecyltrimethylammonium bromide and dodecyltrimethylammonium bromide; i. The phosphate includes at least one of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; j. The concentration of the surfactant in the mixed solution is 1g / L-15g / L.
7. The preparation method according to claim 4, characterized in that: The preparation method satisfies at least one of the following conditions: k. The pH value of the solution after the hydrothermal reaction is 0.2-2; 1. The hydrothermal reaction time is 2h-8h.
8. A lithium iron phosphate positive electrode material, characterized in that: The raw material comprises the iron phosphate precursor described in any one of claims 1 to 3, or the iron phosphate precursor prepared by the preparation method described in any one of claims 4 to 7.
9. A lithium ion battery, characterized in that: The raw materials include the lithium iron phosphate positive electrode material as described in claim 8.